Transcriptional Profiling of Hypo- and Hypervirulent Mycobacterium tuberculosis Isolates Characterised by Differential Expression of the Moa3 Operon - Jon Mitchell Ambler; Matthys Gerhardus Potgieter; Marisa Klopper; Melanie Grobbelaar; Margaretha De Vos; Samantha Sampson; Robin Mark Warren; Jonathan Blackburn; Nicola Mulder (Current Microbiology, 2026)
Despite advances in tuberculosis treatment and prevention, tuberculosis remains a global health threat, responsible for an estimated 1.23 million deaths in 2024 [46], with continued concern over drug-resistant strains. In the Western Cape, South Africa, co-infection of tuberculosis and HIV is a significant public health concern contributing to a higher burden of disease. We compared the transcriptomes of two genetically similar Beijing family strains of Mycobacterium tuberculosis under four different growth conditions, including oxidative stress, using three biological replicates for each isolate. We identified an operon containing genes involved in the biosynthesis of molybdenum cofactor that showed consistently lower levels of expression in the hypervirulent isolate. This pathway is known to play a critical role in numerous metabolic and redox processes, and its dysregulation could contribute to the observed differences in disease severity between the two isolates. The moa genes, which are involved in the biosynthesis of the molybdenum cofactor, have been previously linked to M. tuberculosis virulence through their essential role in redox metabolism and oxidative stress response. Our results support this hypothesis by identifying differential expression of the moa operon as a potential mechanism underlying the differences in disease severity between the two isolates. Furthermore, the minimal genetic differences between these isolates make them an ideal system for further study of this pathway and its contributions to tuberculosis pathogenesis.

Environmental Drivers of Recruitment Variability in Narrow‐Barred Spanish Mackerel Scomberomorus commerson Lacépède, 1800 - Susannah M. Leahy; Joanne Langstreth; Rik C. Buckworth; Peri Subritzky; Olivia J. Whybird; Sam M. Williams; Lucas I. Sumpter; Jonathan D. Mitchell (Fisheries Oceanography, 2026)
Understanding the effects of environmental conditions on fisheries resources is crucial for guiding the effective assessment and management of fish stocks. Previously assessed as depleted, the narrow‐barred Spanish mackerel fishery on the east coast of Queensland, Australia, is under management intervention to rebuild the stock. In this study, we use long‐term age composition data to reconstruct 24 years of historic year class strength and explore a broad range of potential environmental influences on recruitment variability in the fishery. Year class strength was extremely well captured (76%–84% deviance explained) by generalised additive models containing just four environmental indices. Recurring key environmental indices in top models included environmental conditions prior to spawning (large scouring flood events during the wet season before spawning and cool winter sea surface temperature immediately prior to spawning), during spawning (unseasonal flooding near the spawning grounds), during larval dispersal and proxies for food availability for juvenile Spanish mackerel. These results have since been used to hindcast recruitment variability in the fishery prior to the collection of the age‐composition data to better understand historic fluctuations in the fishery, and can also be incorporated into management strategies for rebuilding the stock.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Ten years on: Are raw material criticality assessments making more sense? - Baptiste Andrieu; Benjamin Adams; Mehrnoosh Heydari; Philip Mitchell; Luke Cullen; Alexey Noskov; Julian M. Allwood; André Cabrera Serrenho; Jonathan Cullen (Resources, Conservation and Recycling, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Changes in Adolescent Diet Quality During the Middle to High School Transition - Jessica E. Decker; Knashawn Morales; Emily Moll; Sana Husain; Mary Ellen Vajravelu; Erica C. Jansen; Babette S. Zemel; Jonathan A. Mitchell (Journal of Nutrition Education and Behavior, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Walkable by nature? Adding green and blue space to walkability indices and assessment of socioeconomic inequalities - Lauren Del Rosario; Thomas Astell-Burt; Jonathan R. Olsen; Susan Thompson; Richard Mitchell; Xiaoqi Feng (Environmental Research, 2025)

Offset Between Surface Elevation Table- and Sediment Core-Derived Accretion Rates: Case Study from Piermont Marsh, New York - Clara Chang; Sarah Fernald; Timothy Kenna; Christopher Mitchell; Christina Pacella; Margie Turrin; Jonathan Nichols; Steven Chillrud; Dorothy Peteet (Estuaries and Coasts, 2025)

Park types and equity: Who has access to what? A national assessment of multidimensional park qualities and socioeconomic disparities across Local Authorities in Great Britain - Jess Hepburn; Jonathan R. Olsen; Richard Mitchell; Thomas Astell-Burt; Xiaoqi Feng; Fiona Caryl (Urban Forestry & Urban Greening, 2025)

A seasonal aggregation of juvenile scalloped hammerheads Sphyrna lewini along beaches of the G old C oast, A ustralia - Nicolas Lubitz; Kerryn Doupain; Siobhan Houlihan; Jonathan D. Mitchell (Journal of Fish Biology, 2025)
We document a recurring seasonal aggregation of juvenile scalloped hammerhead sharks Sphyrna lewini along the beaches of the Gold Coast, Australia, with notable occurrences at Burleigh Heads and Kirra Reef. The aggregation consists of individuals of varying sizes, which likely suggests the presence of different cohorts, though it remains uncertain whether this area meets the criteria for a nursery habitat. Given the global population declines of S. lewini , its classification as Critically Endangered by the IUCN and its Conservation Dependent status under Australian legislation, we recommend standardised surveys and tracking studies to assess habitat use, seasonality and the potential role of Gold Coast waters as a critical habitat for juvenile S. lewini .

Geographic, Taxonomic and Metric Gaps in Biodiversity Research Limit Evidence‐Based Conservation in Agricultural Landscapes: An Umbrella Review - Jonathan Bonfanti; Joseph Langridge; A. Avadí; N. Casajus; A. Chaudhary; G. Damour; N. Estrada‐Carmona; S. K. Jones; D. Makowski; M. Mitchell; R. Seppelt; Damien Beillouin (Ecology Letters, 2025)
Agriculture is fundamentally dependent on biodiversity, yet unsustainable management practices increasingly threaten various organisms and ecosystem services. Confronting the global crisis of biodiversity loss requires a thorough understanding of the gaps, clusters and biases in existing knowledge across various management practices, spatial scales, and taxonomic groups. We undertook a comprehensive literature review, synthesising secondary data from 200 meta‐analyses on agricultural management impacts on biodiversity in croplands. Our systematic map covers 1885 comparisons (mean effect sizes), from over 9000 primary studies. In the latter, seven high‐income countries prevail (notably the USA, China and Brazil), with particular focus on fertiliser use, phytosanitary interventions and crop diversification. This emphasis on individual practices overshadows research at the farm and landscape levels. In secondary evidence, arthropods and microorganisms are most frequently studied, while annelids, vertebrates and plants are less represented. Evidence predominantly stems from averaged abundance data, revealing substantial gaps in studies on functional and phylogenetic diversity. Our findings highlight the need to analyse combinations of multiple practices to accurately reflect real‐world farming contexts, and covering a wider range of taxa, biodiversity metrics and spatial levels, to enable evidence‐based conservation strategies in agriculture. Given the uneven evidence on agricultural impacts, caution is required when applying meta‐analytical findings to public policies and global assessments.

High-resolution mapping of shark movements from drone footage at Queensland beaches improves risk assessment for beach safety - Maddison Cross; Jonathan Mitchell; Tracey Scott-Holland (Marine Policy, 2025)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Grounding Soil Carbon Sequestration Claims: The Role of Long‐Term EC Flux Data - Elaine Mitchell; David Rowlings; Jonathan Sanderman (Global Change Biology, 2025)

Organochlorine pesticide use and mosaic loss of chromosome Y in a study of male farmers - Lauren M. Hurwitz; Vicky C. Chang; Laura E. Beane Freeman; Mitchell J. Machiela; Weiyin Zhou; Gabriella Andreotti; Christine G. Parks; Dale P. Sandler; Nathaniel Rothman; Sonja I. Berndt; Jonathan N. Hofmann; Stella Koutros (Environmental Research, 2025)

Occupational pesticide use and relative leukocyte telomere length in the biomarkers of exposure and effect in agriculture study - Patricia A. Erickson; Vicky C. Chang; Shisi He; Casey Dagnall; Kedest Teshome; Mitchell J. Machiela; Kathryn Hughes Barry; Edna F.R. Pereira; Shahinaz M. Gadalla; Christine G. Parks; Sonja I. Berndt; Laura E. Beane Freeman; et al. (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Distribution and disturbances of ditches across salt marshes of the Northeast U.S. with implications for management and restoration - Erin K. Peck; Julie E. Walker; Katherine V. Ackerman; Joel Carr; Maureen D. Correll; Zafer Defne; Linda A. Deegan; Mitchell J. Eaton; Neil K. Ganju; Mitch Hartley; Catherine Johnson; Jason Mercer; et al. (Journal of Environmental Management, 2025)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Applying acoustic telemetry, vessel tracking and fisher knowledge to investigate and manage fisher-shark conflict at Lord Howe Island, Australia - Jonathan D. Mitchell; Victoria Camilieri-Asch; Sallyann Gudge; Fabrice R. A. Jaine; Victor M. Peddemors; Tim J. Langlois (Marine Biology, 2024)
Fisher-shark conflict is occurring at Lord Howe Island, Australia due to high levels of Galapagos shark ( Carcharhinus galapagensis ) depredation (where sharks consume hooked fish) and bycatch. Depredation causes costly loss of target catch and fishing gear and increased mortality of target species, and sharks can be injured or killed when bycaught. This study applied acoustic telemetry and vessel tracking from 2018 to 2021 to identify; (1) how the movements of 30 tagged sharks and activity of six fishing vessels overlapped, and (2) where key ‘hotspots’ of overlap occurred. Fisher surveys were also conducted to collect information about mitigating shark interactions. Residency index analysis indicated that three sharks tagged at a fish waste dumping site had markedly higher residency. Core home ranges of sharks overlapped with higher fishing activity at four ‘hotspots’. Statistical modelling indicated positive linear effects of fishing activity and bathymetric complexity on shark detections and tagged sharks were present for 13% of the total time that vessels were fishing close to acoustic receivers. Spatio-temporal overlaps between shark movements and fishing activity could potentially have occurred because sharks learned to associate fishing vessels with food (i.e. hooked fish) and because fishers and sharks utilise highly productive shelf edge areas, however more research is needed to investigate these relationships. Fishers reported that rotating fishing areas and reducing time at each location, fishing deeper than 100 m, and using electric reels and lures instead of bait, reduced bycatch and depredation. The integrated approach used here identified practical methods for reducing fisher-shark conflict, improving socio-economic outcomes for fishers and conservation prospects for this unique shark population.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

Understanding factors influencing farmers’ crop choice and agricultural transformation in the Upper Vietnamese Mekong Delta - Thi Ha Lien Le; Paul Kristiansen; Brenda Vo; Jonathan Moss; Mitchell Welch (Agricultural Systems, 2024)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Optimal heat stress metric for modelling heat‐related mortality varies from country to country - Y. T. Eunice Lo; Dann M. Mitchell; Jonathan R. Buzan; Jakob Zscheischler; Rochelle Schneider; Malcolm N. Mistry; Jan Kyselý; Éric Lavigne; Susana Pereira da Silva; Dominic Royé; Aleš Urban; Ben Armstrong; et al. (International Journal of Climatology, 2023)
Combined heat and humidity is frequently described as the main driver of human heat‐related mortality, more so than dry‐bulb temperature alone. While based on physiological thinking, this assumption has not been robustly supported by epidemiological evidence. By performing the first systematic comparison of eight heat stress metrics (i.e., temperature combined with humidity and other climate variables) with warm‐season mortality, in 604 locations over 39 countries, we find that the optimal metric for modelling mortality varies from country to country. Temperature metrics with no or little humidity modification associates best with mortality in ~40% of the studied countries. Apparent temperature (combined temperature, humidity and wind speed) dominates in another 40% of countries. There is no obvious climate grouping in these results. We recommend, where possible, that researchers use the optimal metric for each country. However, dry‐bulb temperature performs similarly to humidity‐based heat stress metrics in estimating heat‐related mortality in present‐day climate.

Ocean carbon from space: Current status and priorities for the next decade - Robert J.W. Brewin; Shubha Sathyendranath; Gemma Kulk; Marie-Hélène Rio; Javier A. Concha; Thomas G. Bell; Astrid Bracher; Cédric Fichot; Thomas L. Frölicher; Martí Galí; Dennis Arthur Hansell; Tihomir S. Kostadinov; et al. (Earth-Science Reviews, 2023)

Measuring the immeasurable: A structural equation modeling approach to assessing soil health - Tai McClellan Maaz; Ronald H. Heck; Christine Tallamy Glazer; Mitchell K. Loo; Johanie Rivera Zayas; Aleric Krenz; Tanner Beckstrom; Susan E. Crow; Jonathan L. Deenik (Science of The Total Environment, 2023)

Neither myonuclear accretion nor a myonuclear domain size ceiling is a feature of the attenuated hypertrophic potential of aged human skeletal muscle - Matthew S. Brook; Daniel J. Wilkinson; Janelle Tarum; Kyle W. Mitchell; Jonathan L. Lund; Bethan E. Phillips; Nathaniel J. Szewczyk; Fawzi Kadi; Paul L. Greenhaff; Ken Smith; Philip J. Atherton (GeroScience, 2023)
Ageing limits growth capacity of skeletal muscle (e.g. in response to resistance exercise), but the role of satellite cell (SC) function in driving this phenomenon is poorly defined. Younger (Y) (~ 23 years) and older (O) men (~ 69 years) (normal-weight BMI) underwent 6 weeks of unilateral resistance exercise training (RET). Muscle biopsies were taken at baseline and after 3-/6-week training. We determined muscle size by fibre CSA (and type), SC number, myonuclei counts and DNA synthesis (via D 2 O ingestion). At baseline, there were no significant differences in fibre areas between Y and O. RET increased type I fibre area in Y from baseline at both 3 weeks and 6 weeks (baseline: 4509 ± 534 µm 2 , 3 weeks; 5497 ± 510 µm 2 P < 0.05, 6 weeks; 5402 ± 352 µm 2 P < 0.05), whilst O increased from baseline at 6 weeks only (baseline 5120 ± 403 µm 2 , 3 weeks; 5606 ± 620 µm 2 , 6 weeks; 6017 ± 482 µm 2 P < 0.05). However, type II fibre area increased from baseline in Y at both 3 weeks and 6 weeks (baseline: 4949 ± 459 µm 2 , 3 weeks; 6145 ± 484 µm 2 ( P < 0.01), 6 weeks; 5992 ± 491 µm 2 ( P < 0.01), whilst O showed no change (baseline 5210 ± 410 µm 2 , 3 weeks; 5356 ± 535 µm 2 ( P = 0.9), 6 weeks; 5857 ± 478 µm 2 ( P = 0.1). At baseline, there were no differences in fibre myonuclei number between Y and O. RET increased type I fibre myonuclei number from baseline in both Y and O at 3 weeks and 6 weeks with RET (younger: baseline 2.47 ± 0.16, 3 weeks; 3.19 ± 0.16 ( P < 0.001), 6 weeks; 3.70 ± 0.29 ( P < 0.0001); older: baseline 2.29 ± 0.09, 3 weeks; 3.01 ± 0.09 ( P < 0.001), 6 weeks; 3.65 ± 0.18 ( P < 0.0001)). Similarly, type II fibre myonuclei number increased from baseline in both Y and O at 3 weeks and 6 weeks (younger: baseline 2.49 ± 0.14, 3 weeks; 3.31 ± 0.21 ( P < 0.001), 6 weeks; 3.86 ± 0.29 ( P < 0.0001); older: baseline 2.43 ± 0.12, 3 weeks; 3.37 ± 0.12 ( P < 0.001), 6 weeks; 3.81 ± 0.15 ( P < 0.0001)). DNA synthesis rates %.d −1 exhibited a main effect of training but no age discrimination. Declines in myonuclei addition do not underlie impaired muscle growth capacity in older humans, supporting ribosomal and proteostasis impairments as we have previously reported.

Relating QRS voltages to left ventricular mass and body composition in elite endurance athletes - Ruben De Bosscher; Jonathan Moeyersons; Christophe Dausin; Mathias Claeys; Kristel Janssens; Piet Claus; Kaatje Goetschalckx; Jan Bogaert; Caroline M. Van De Heyning; Bernard Paelinck; Prashanthan Sanders; Jonathan Kalman; et al. (European Journal of Applied Physiology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

The Cerebellum and Implicit Sequencing: Evidence from Cerebellar Ataxia - Owen P. Morgan; Mitchell B. Slapik; Katherine G. Iannuzzelli; Stephen M. LaConte; Jonathan M. Lisinski; Peg C. Nopoulos; Ashley M. Cochran; Sharif I. Kronemer; Liana S. Rosenthal; Cherie L. Marvel (The Cerebellum, 2021)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Assessing ecosystem service trade-offs and synergies: The need for a more mechanistic approach - Marie C. Dade; Matthew G.E. Mitchell; Clive A. McAlpine; Jonathan R. Rhodes (Ambio, 2019)

Global environmental change effects on plant community composition trajectories depend upon management legacies - Michael P. Perring; Markus Bernhardt‐Römermann; Lander Baeten; Gabriele Midolo; Haben Blondeel; Leen Depauw; Dries Landuyt; Sybryn L. Maes; Emiel De Lombaerde; Maria Mercedes Carón; Mark Vellend; Jörg Brunet; et al. (Global Change Biology, 2018)
The contemporary state of functional traits and species richness in plant communities depends on legacy effects of past disturbances. Whether temporal responses of community properties to current environmental changes are altered by such legacies is, however, unknown. We expect global environmental changes to interact with land‐use legacies given different community trajectories initiated by prior management, and subsequent responses to altered resources and conditions. We tested this expectation for species richness and functional traits using 1814 survey‐resurvey plot pairs of understorey communities from 40 European temperate forest datasets, syntheses of management transitions since the year 1800, and a trait database. We also examined how plant community indicators of resources and conditions changed in response to management legacies and environmental change. Community trajectories were clearly influenced by interactions between management legacies from over 200 years ago and environmental change. Importantly, higher rates of nitrogen deposition led to increased species richness and plant height in forests managed less intensively in 1800 (i.e., high forests), and to decreases in forests with a more intensive historical management in 1800 (i.e., coppiced forests). There was evidence that these declines in community variables in formerly coppiced forests were ameliorated by increased rates of temperature change between surveys. Responses were generally apparent regardless of sites’ contemporary management classifications, although sometimes the management transition itself, rather than historic or contemporary management types, better explained understorey responses. Main effects of environmental change were rare, although higher rates of precipitation change increased plant height, accompanied by increases in fertility indicator values. Analysis of indicator values suggested the importance of directly characterising resources and conditions to better understand legacy and environmental change effects. Accounting for legacies of past disturbance can reconcile contradictory literature results and appears crucial to anticipating future responses to global environmental change.

The Scale-Dependent Role of Biological Traits in Landscape Ecology: A Review - Andrés Felipe Suárez-Castro; Jeremy S. Simmonds; Matthew G. E. Mitchell; Martine Maron; Jonathan R. Rhodes (Current Landscape Ecology Reports, 2018)

Erratum to: What drives national support for multilateral climate finance? International and domestic influences on Australia’s shifting stance - Jonathan Pickering; Paul Mitchell (International Environmental Agreements: Politics, Law and Economics, 2017)

What drives national support for multilateral climate finance? International and domestic influences on Australia’s shifting stance - Jonathan Pickering; Paul Mitchell (International Environmental Agreements: Politics, Law and Economics, 2017)

Using high-resolution LiDAR data to quantify the three-dimensional structure of vegetation in urban green space - Rhiannon J. C. Caynes; Matthew G. E. Mitchell; Dan Sabrina Wu; Kasper Johansen; Jonathan R. Rhodes (Urban Ecosystems, 2016)

Estimated lead (Pb) exposures for a population of urban community gardeners - Henry M. Spliethoff; Rebecca G. Mitchell; Hannah Shayler; Lydia G. Marquez-Bravo; Jonathan Russell-Anelli; Gretchen Ferenz; Murray McBride (Environmental Geochemistry and Health, 2016)

Acute response to cluster sets in trained and untrained men - Jonathan M. Oliver; Andreas Kreutzer; Shane Jenke; Melody D. Phillips; Joel B. Mitchell; Margaret T. Jones (European Journal of Applied Physiology, 2015)

Territoriality in a snake - Jonathan K. Webb; Mitchell L. Scott; Martin J. Whiting; Richard Shine (Behavioral Ecology and Sociobiology, 2015)

Drivers of temporal changes in temperate forest plant diversity vary across spatial scales - Markus Bernhardt‐Römermann; Lander Baeten; Dylan Craven; Pieter De Frenne; Radim Hédl; Jonathan Lenoir; Didier Bert; Jörg Brunet; Markéta Chudomelová; Guillaume Decocq; Hartmut Dierschke; Thomas Dirnböck; et al. (Global Change Biology, 2015)
Global biodiversity is affected by numerous environmental drivers. Yet, the extent to which global environmental changes contribute to changes in local diversity is poorly understood. We investigated biodiversity changes in a meta‐analysis of 39 resurvey studies in European temperate forests (3988 vegetation records in total, 17–75 years between the two surveys) by assessing the importance of (i) coarse‐resolution (i.e., among sites) vs. fine‐resolution (i.e., within sites) environmental differences and (ii) changing environmental conditions between surveys. Our results clarify the mechanisms underlying the direction and magnitude of local‐scale biodiversity changes. While not detecting any net local diversity loss, we observed considerable among‐site variation, partly explained by temporal changes in light availability (a local driver) and density of large herbivores (a regional driver). Furthermore, strong evidence was found that presurvey levels of nitrogen deposition determined subsequent diversity changes. We conclude that models forecasting future biodiversity changes should consider coarse‐resolution environmental changes, account for differences in baseline environmental conditions and for local changes in fine‐resolution environmental conditions.

Individual- and neighborhood-level education influences the effect of obesity on prostate cancer treatment failure after prostatectomy - Charnita Zeigler-Johnson; Knashawn H. Morales; Karen Glanz; Elaine Spangler; Jonathan Mitchell; Timothy R. Rebbeck (Cancer Causes & Control, 2015)

Plant diversity predicts beta but not alpha diversity of soil microbes across grasslands worldwide - Suzanne M. Prober; Jonathan W. Leff; Scott T. Bates; Elizabeth T. Borer; Jennifer Firn; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Elsa E. Cleland; Nicole M. DeCrappeo; et al. (Ecology Letters, 2015)
Aboveground–belowground interactions exert critical controls on the composition and function of terrestrial ecosystems, yet the fundamental relationships between plant diversity and soil microbial diversity remain elusive. Theory predicts predominantly positive associations but tests within single sites have shown variable relationships, and associations between plant and microbial diversity across broad spatial scales remain largely unexplored. We compared the diversity of plant, bacterial, archaeal and fungal communities in one hundred and forty‐five 1 m 2 plots across 25 temperate grassland sites from four continents. Across sites, the plant alpha diversity patterns were poorly related to those observed for any soil microbial group. However, plant beta diversity (compositional dissimilarity between sites) was significantly correlated with the beta diversity of bacterial and fungal communities, even after controlling for environmental factors. Thus, across a global range of temperate grasslands, plant diversity can predict patterns in the composition of soil microbial communities, but not patterns in alpha diversity.

Heart rate response at the onset of exercise in an apparently healthy cohort - Allison Jagoda; Jonathan N. Myers; Leonard A. Kaminsky; Mitchell H. Whaley (European Journal of Applied Physiology, 2014)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Using multilevel models to identify drivers of landscape‐genetic structure among management areas - Rachael Y. Dudaniec; Jonathan R. Rhodes; Jessica Worthington Wilmer; Mitchell Lyons; Kristen E. Lee; Clive A. McAlpine; Frank N. Carrick (Molecular Ecology, 2013)
Landscape genetics offers a powerful approach to understanding species' dispersal patterns. However, a central obstacle is to account for ecological processes operating at multiple spatial scales, while keeping research outcomes applicable to conservation management. We address this challenge by applying a novel multilevel regression approach to model landscape drivers of genetic structure at both the resolution of individuals and at a spatial resolution relevant to management (i.e. local government management areas: LGA s) for the koala ( Phascolartos cinereus ) in Australia. Our approach allows for the simultaneous incorporation of drivers of landscape‐genetic relationships operating at multiple spatial resolutions. Using microsatellite data for 1106 koalas, we show that, at the individual resolution, foliage projective cover ( FPC ) facilitates high gene flow (i.e. low resistance) until it falls below approximately 30%. Out of six additional land‐cover variables, only highways and freeways further explained genetic distance after accounting for the effect of FPC . At the LGA resolution, there was significant variation in isolation‐by‐resistance ( IBR ) relationships in terms of their slopes and intercepts. This was predominantly explained by the average resistance distance among LGA s, with a weaker effect of historical forest cover. Rates of recent landscape change did not further explain variation in IBR relationships among LGA s. By using a novel multilevel model, we disentangle the effect of landscape resistance on gene flow at the fine resolution (i.e. among individuals) from effects occurring at coarser resolutions (i.e. among LGA s). This has important implications for our ability to identify appropriate scale‐dependent management actions.

Remucal et al. Respond: - Jonathan M. Remucal; Jason D. McGee; Matthew M. Fehrenbacher; Constance Best; Robert J. Mitchell (Journal of Forestry, 2013)

Quantitative In Situ Enhanced Oil Recovery Monitoring Using Nuclear Magnetic Resonance - Jonathan Mitchell; John Staniland; Romain Chassagne; Edmund J. Fordham (Transport in Porous Media, 2012)

Seroprevalence of seasonal and pandemic influenza A viruses in domestic cats - Jonathan A. McCullers; Lee-Ann Van De Velde; Ronald D. Schultz; Cristen G. Mitchell; C. R. Halford; Kelli L. Boyd; Stacey Schultz-Cherry (Archives of Virology, 2011)

Grooves to tubes: evolution of the venom delivery system in a Late Triassic “reptile” - Jonathan S. Mitchell; Andrew B. Heckert; Hans-Dieter Sues (The Science of Nature, 2010)

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

Phylogenomic Analysis of the α Proteasome Gene Family from Early-Diverging Eukaryotes - Juan L. Bouzatrid="*"rid="†"; Leslie K. McNeilrid="*"; Hugh M. Robertson; Leellen F. Solter; Julie E. Nixon; Jonathan E. Beever; H. Rex Gaskins; Gary Olsen; Shankar Subramaniam; Mitchell L. Sogin; Harris A. Lewin (Journal of Molecular Evolution, 2000)